Electronic Structure of trans-[VIICl2(E(CH3)2CH2CH2E(CH3)2)2], E=N, P - Jafari, Mehrafshan G.; Zolnhofer, Eva; Fehn, Dominik; Heinemann, Frank Wilhelm; Opalade, Adedamola A.; Carroll, Patrick J.; Meyer, Karsten; Krzystek, J.; Ozarowski, Andrew; Mindiola, Daniel J.; Jackson, Timothy A.; Telser, Joshua (European Journal of Inorganic Chemistry, 2024)
Coordination complexes of general formula trans-[MX2(R2ECH2CH2ER2)2] (MII=Ti, V, Cr, Mn; E=N or P; R=alkyl or aryl) are a cornerstone of coordination and organometallic chemistry. We investigate the electronic properties of two such complexes, trans-[VCl2(tmeda)2] and trans-[VCl2(dmpe)2], which thus represent trans-[MX2(R2ECH2CH2ER2)2] where M=V, X=Cl, R=Me and E=N (tmeda) and P (dmpe). These VII complexes have S=3/2 ground states, as expected for octahedral d3. Their tetragonal distortion leads to zero-field splitting (zfs) that is modest in magnitude (D≈0.3 cm−1) relative to analogous S=1 TiII and CrII complexes. This parameter was determined from conventional EPR spectroscopy, but more effectively from high-frequency and -field EPR (HFEPR) that determined the sign of D as negative for the diamine complex, but positive for the diphosphine, which information had not been known for any trans-[VX2(R2ECH2CH2ER2)2] systems. The ligand-field parameters of trans-[VCl2(tmeda)2] and trans-[VCl2(dmpe)2] are obtained using both classical theory and ab initio quantum chemical theory. The results shed light not only on the electronic structure of VII in this environment, but also on differences between N and P donor ligands, a key comparison in coordination chemistry.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Diamines; Diphosphines; EPR; Ligand-field theory; Quantum chemistry